Evaluasi Pelaksanaan Program Peningkatan Kesehatan BPJS Pada Puskesmas Wua-Wua Kota Kendari - Riswana, Risky; Kambolong, Makmur; Sahrun, Sahrun (Universitas Halu Oleo, 2020)
The purpose of this study was to determine the implementation of the BPJS health improvement program at the Wua-Wua Health Center, Kendari City. The research method used is descriptive qualitative method. The results showed that the evaluation of the implementation of the BPJS Program at the Wua-Wua Community Health Center was carried out by paying attention to good service and there were also ongoing evaluations, especially those that were still lacking and still needed to be improved in terms of existing facilities and infrastructure as well as existing programs at the Puskesmas Wua-Wua, namely the prolanis program and also JKN. The program still needs to be improved, which means that the evaluation must also be improved. At the Wua-Wua Puskesmas, Kendari City, every month a mini workshop is held, which is then carried out an evaluation there. For the Determination of objectives in evaluation, the basic thing that is still lacking and still needs to be improved is the long queue so that the patient feels the need for improvement in this aspect and then for the determination of facilities, namely the lack of facilities and evaluation in this case is still lacking.